Chlorzoxazone reduced the paracetamol-induced toxicity via competitive inhibition of CYP2E1-mediated metabolism - Ravindra Babu Pingili; Sridhar Vemulapalli; Manideep V. V. N. Gadamsetty; Divya Presingu; Ruthvik Katuri; Vijayalakshmi Rachamsetty; Naveen Babu Kilaru (SpringerOpen, 2023)
Abstract Background Drug metabolism is crucial to attaining the therapeutic index of any drug. The metabolism and elimination of the drugs are governed mainly by P-glycoprotein (P-gp) and Cytochrome P450 (CYP). Paracetamol is mostly used as analgesic and antipyretic agent. The metabolism of paracetamol is primarily via Glucuronidation and sulphation at therapeutic doses. About 5-10% of paracetamol is metabolized via CYP mediated pathway. Cytochrome P450 2E1 (CYP2E1) is primarily responsible for forming a toxic metabolite of paracetamol called N-acetyl-p-benzoquinoneimine (NAPQI). Even at therapeutic doses, long-term usage of paracetamol leads to the hepatic and nephrotoxicity because of NAPQI. Several in-vitro and in-vivo studies conducted by different research groups and reported that chlorzoxazone is a substrate and inhibitor of CYP2E1. However, the effect of chlorzoxazone on the paracetamol (CYP2E1 substrate) metabolism via the CYP2E1 has not yet been reported. This study investigated the effect of chlorzoxazone on the CYP2E1-mediated metabolism of Paracetamol and NAPQI formation in Wistar rats. Results For 15 days, animals were orally administered with Paracetamol (300 mg/kg) with and without Silymarin (100 mg/kg) (standard CYP2E1 inhibitor) and Chlorzoxazone (50 and 100 mg/kg). Analysis was performed using RP-HPLC on the 15th day to determine paracetamol and NAPQI concentration in the plasma. Paracetamol combination with chlorzoxazone (50 and 100 mg/kg) showed a dose-dependent increase in the AUC0-∞ and the peak plasma concentration (Cmax) of Paracetamol and a dose-dependent decrease of AUC0-∞ and Cmax of NAPQI compared to paracetamol control (p < 0.001). Chlorzoxazone significantly decreased the elevated liver and renal markers compared to paracetamol control. Simultaneously, Hepatic and nephrotic tissue studies showed that compared to the paracetamol control group, the combination of chlorzoxazone significantly ameliorated paracetamol-induced hepatotoxicity and nephrotoxicity. Conclusion Finally, this study revealed that paracetamol in combination with chlorzoxazone led to a significant decrease in the plasma levels of NAPQI and enhanced absorption of paracetamol in rats via the inhibition of CYP2E1- mediated metabolism. In addition, chlorzoxazone significantly ameliorated paracetamol-induced hepatotoxicity and nephrotoxicity.